Visualization of Gerota Fascia Involved With Metastatic Melanoma on FDG PET/CT - Gary A. Ulaner; Pete Giuliano (Clinical Nuclear Medicine, 2026)
A 67-year-old man with melanoma underwent FDG PET/CT demonstrating FDG-avid curvilinear soft tissue anterior, lateral, and posterior to the left kidney. This soft tissue structure is Gerota fascia, a fibrous sheath encasing the kidneys, adrenal glands, and adjacent fat, which protects these structures from trauma and is a barrier to the spread of hemorrhage and infection. This case demonstrates an important anatomic structure not commonly visualized on FDG PET/CT, identified here due to involvement with malignancy. Physicians interpreting FDG PET/CT should be aware of the location and function of Gerota fascia, as well as its appearance when pathologically involved.